Development of a reversed dispersive based graphene functionalized with multiwalled carbon nanotubes for detection of β2-agonists in pork by high-performance liquid chromatography - Ying-Wen Qian; Xia Hong; Cai-Xia Yuan; Xin-Kui Zhou; Hai-Ning He; Dong-Shuai Wang (Food Science and Human Wellness)
A reliable and inexpensive pretreatment procedure in the determination of β2-agonists in pork was developped. The procedure used a nanocomposite of multiwalled carbon nanotubes (CNTs) functionalized with graphene (rGO) as the reversed dispersive sorbent. It was analyzed after purification by high-performance liquid chromatography, the extraction time and the properties of the nanocomposite were optimized. Under optimized conditions, present method has linear response over concentration range of 0.5–50 ng/mL in pork samples with a satisfactory detection limit close to 0.1 ng/mL. The precisions of the current method (coefficient of variation) are lower than 5%, while recoveries are more than 98.3%. The nanocomposite exhibited high adsorptivity, long-term storage stability, satisfactory anti-interfering activity and high selectivity toward β2-agonists compared with those of rGO and CNTs. Keywords: High-performance liquid chromatography, Graphene, Multiwalled carbon nanotube, Ractopamine, Salbutamol